Visualizing the cell biology of civic science - Fanuel Muindi (724759) (2025)
This schematic illustrates a conceptual model for understanding civic science through the logic of cell biology. Key actors in the civic science ecosystem are represented as intracellular organelles, including scholars (nucleus), funders (mitochondria), practitioners (ribosomes), training initiatives (endoplasmic reticulum), organizations (golgi apparatus), conveners (centrioles), and regulators (endosomes). Signals originating from communities in the extracellular space interact with receptors on the cell membrane, triggering pathways that move through the practice environment (cytosol) and yield diverse forms of civic science practice such as science communication, participatory science, science policy, and informal science. This mock-up offers an initial visualization of the actors, interactions, and processes that constitute the cell biology of civic science.